VOCATION AND CREATION: BEYOND THE GENTILE-HOMOSEXUAL ANALOGY - Perry, John (Journal of religious ethics, 2012)
One strand of the church's conversation about homosexuality compares present-day acceptance of homosexuals to the church's acceptance of Gentiles in Acts 15. In a previous article, “Gentiles and Homosexuals,” I presented the history of that strand. In a reply to my article, Olson proposes to reimagine the analogy via the “radical new perspective on Paul” and argues that doing so exposes problems with my original analysis. I defend myself against these criticisms, while also entering into the spirit of Olson's reimagined analogy. Expanding the scope beyond Acts to Paul opens up important facets that might otherwise be obscured. In particular, it includes voices that are sometimes silenced, and presses both sides for an account of sexuality grounded in vocation and God's purposes in creation.